Learning Model “AWAS (Activity Watch And See) In Increasing Motivation To Learn Geography In Class XI IPS 1 SMA Negeri 1 Gantung - M. Aruna M. Aruna; Eviliyanto Eviliyanto (Universitas Veteran Bangun Nusantara, 2022)
The main problems that will be solved through this Classroom Action Research are: Are The “AWAS (Activity Watch And See)” Learning Model Can Increase Learning Motivation Geography In Class XI 1 IPS SMA NEGERI 1 GANTUNG for the 2020/2021 academic year. The